Ruthenium(II) phosphine/diimine/picolinate complexes: Inorganic compounds as agents against tuberculosis - Pavan, Fernando Rogério [UNESP]; Poelhsitz, Gustavo V.; Barbosa, Marilia I. F.; Leite, Sergio R. A. [UNESP]; Batista, Alzir A.; Ellena, Javier; Sato, Leticia S. [UNESP]; Franzblau, Scott G.; Moreno, Virtudes; Gambino, Dinorah; Leite, Clarice Queico Fujimura [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2011)
This paper describes the synthesis and characterization of four new ruthenium complexes containing 1,4 bis(diphenylphosphino)butane (dppb), 2-pyridinecarboxylic acid anion (pic) and the diimines [(2,2'-bipyridine (bipy), 4,4'-dimethyl-2,2'-bipyridine (Me-bipy), 4,4'-dichloro-2,2'-bipyridine (Cl-bipy) and 1,10-phenanthroline (phen) as ligands, with formulae [Ru(pic)(dppb)(bipy)]PF6 (SCAR01), [Ru(pic)(dppb) (Me-bipy)]PF6 (SCAR02), [Ru(Pic)(dPPb)(Cl-bipy]PF6 (SCAR03) and [Ru(pic)(dppb)(phen)]PF6 (SCAR04). Additionally, the in vitro anti-Mycobacterium tuberculosis (MTB) activity, cytotoxicity and activity against in vitro infection of these complexes and two more complexes, cis-[Ru(pic)(dppe)(2)]PF6(SCAR05) and cis-[RuCl2(dppb)(bipy)] (SCAR06), and their free ligands are described and discussed. All compounds showed excellent MIC against MTB, low cytotoxicity and a selectivity index higher than 10. Also, all compounds showed significant intracellular inhibition and the compound SCAR05 showed a better activity than rifampin and SQ109. This is the first report of activity against in vitro infection of ruthenium compounds. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: Mycobacterium tuberculosis; Drug resistance; Ruthenium; Phosphine/diimine/picolinate